Letter : Mr. H. Graham - Midgley, Harry, d. 1957
013-0033-001 Alderman Harry Midgley. J.P. 19 Garfield Chambers, Belfast. Dear Mr. Tewson, 9th Sept, 1941 Re. Mr. H. Graham I thank you for your letter of 1st inst, Ref. VF/MN/737, re above; also Mr McCarthy for his letter of 29th ultimo. I have asked Mrs Graham to do her best to find out the particulars you ask for and when these are forthcoming I will write you. With kind regards and best wishes for the welfare of all our British comrades in these trying times. Yours sincerely, Harry Midgley. AC. 292/946/13/33